Absolute Measurement of Domain Composition and Nanoscale Size Distribution Explains Performance in PTB7:PC71BM Solar Cells. Issue 1 (1st October 2012) - Collins, Brian A.; Li, Zhe; Tumbleston, John R.; Gann, Eliot; McNeill, Christopher R.; Ade, Harald
Abstract The importance of morphology to organic solar cell performance is well known, but to date, the lack of quantitative, nanoscale and statistical morphological information has hindered obtaining direct links to device function. Here resonant X‐ray scattering and microscopy are combined to quantitatively measure the nanoscale domain size, distribution and composition in high efficiency solar cells based on PTB7 and PC71BM. The results show that the solvent additive diiodooctane dramatically shrinks the domain size of pure fullerene agglomerates that are embedded in a polymer‐rich 70/30 wt.% molecularly mixed matrix, while preserving the domain composition relative to additive‐free devices. The fundamental miscibility between the species – measured to be equal to the device's matrix composition – is likely the dominant factor behind the overall morphology with the additive affecting the dispersion of excess fullerene. As even the molecular ordering measured by X‐ray diffraction is unchanged between the two processing routes the change in the distribution of domain size and therefore increased domain interface is primarily responsible for the dramatic increase in device performance. While fullerene exciton harvesting is clearly one significant cause of the increase owing to smaller domains, a measured increase in harvesting from the polymer species indicates that the molecular mixing is not the reason for the high efficiency in this system. Rather, excitations in the polymer likely require proximity to a pure fullerene phase for efficient charge separation and transport. Furthermore, in contrast to previous measurements on a PTB7‐based system, a hierarchical morphology was not observed, indicating that it is not necessary for high performance.